Conjugated ionic (co)polythiophene-based cathode interlayers for bulk heterojunction organic solar cells. (December 2017) - Govaerts, Sanne; Kesters, Jurgen; Defour, Maxime; Van Mele, Bruno; Penxten, Huguette; Neupane, Shova; Renner, Frank Uwe; Lutsen, Laurence; Vanderzande, Dirk; Maes, Wouter
Graphical abstract: Highlights: A series of random and block copolythiophene polyelectrolytes is synthesized. The ionic polythiophenes are applied as cathode interlayers in polymer solar cells. An average increase in power conversion efficiency of 15% is realized. Structure-performance relations are investigated. The efficiency gain is rather general for various topologies and compositions. Abstract: The incorporation of conjugated polyelectrolytes as cathode interlayers in organic photovoltaics has been proven to be an effective way to boost the device efficiency. Nevertheless, more detailed investigations of the structure–property relationships of these interlayer materials, in particular related to the film deposition behavior, can provide further insights into their mode of action. With this aim, a series of ionic (co)polythiophenes is successfully synthesized via Kumada catalyst-transfer condensation polymerization and subsequent introduction of ionic moieties on the polymer side chains. Both the topology (i.e. homopolymers, random and block copolymers) and the amount of ionic groups are systematically varied. The polymers are fully characterized and then applied as cathode interlayers in polymer solar cells based on PCDTBT:PC71 BM, affording an average efficiency increase of ∼15%. The structural screening on one hand indicates that the efficiency gain is a rather general phenomenon for this material class. On the other hand, the best photovoltaic responses are observed for the conjugated polyelectrolytes with a higher triethylene glycol side chain ratio and the block copolymer structure performs slightly better as compared to the random copolymer with the same (50/50) monomer ratio. Based on these findings, the field can move on to a more rational development of novel interfacial materials and thereby push the device efficiency even further.